Hierarchical silicalite-1 octahedra comprising highly-branched orthogonally-stacked nanoplates as efficient catalysts for vapor-phase Beckmann rearrangement. Issue 80 (16th September 2016) - Chang, Albert; Hsiao, Hsu-Ming; Chen, Tsai-Hsiu; Chu, Ming-Wen; Yang, Chia-Min
Abstract : A structure-directing agent was designed to synthesize hierarchical silicalite-1 octahedra comprising highly-branched and orthogonally-stacked nanoplates that exhibited excellent and stable activity for Beckmann rearrangement of cyclic oximes and high lactam selectivity. Abstract : A triblock structure-directing agent was designed to synthesize hierarchical silicalite-1 octahedra comprising highly-branched, orthogonally-stacked and self-pillared nanoplates that exhibited excellent and stable activity for the vapor-phase Beckmann rearrangement of cyclic oximes and high lactam selectivity.